Analysis of Constraints in Adoption of Mushroom Cultivation in Bihar (Indian Journal of Extension Education, 2018)
Mushroom cultivation is one of the agricultural activity in which rural youth can play a vital role without sacrificing their household responsibilities to add good quality protein in their daily diets and by helping hand in malnutrition abolition. Vocational training programme was imparted during the year 2012-13 to 2014-15 by the Department of Plant Pathology, Bihar Agricultural College, BAU, Sabour, Bihar. 25 person were selected for participation in each programme. After each training programme data of number of mushroom units established and adoption rate of mushroom cultivation were collected from the trainees. According to this data 43, 63 and 54 mushroom units were established with adoption rate, 46.74, 52.00 and 57.00 per cent during the year 2012-13, 2013-14 and 2014-15, respectively. Major possible constraints such as technological constraints, economical constraints and marketing constraints were also evaluated in this study. Lack of proper marketing support and unavailability of quality spawn was the most significant constraint which was accountable for slower adoption. Inadequate knowledge about mushroom cultivation, lack of government policies, and transfer of technology were the other major hindrance in this progression.